Assessment of Bone Fragility in Patients With Multiple Myeloma Using QCT‐Based Finite Element Modeling. (7th September 2016) - Campbell, Graeme M; Peña, Jaime A; Giravent, Sarah; Thomsen, Felix; Damm, Timo; Glüer, Claus‐C; Borggrefe, Jan
ABSTRACT: Multiple myeloma (MM) is a malignant plasma cell disease associated with severe bone destruction. Surgical intervention is often required to prevent vertebral body collapse and resulting neurological complications; however, its necessity is determined by measuring lesion size or number, without considering bone biomechanics. Finite element (FE) modeling, which simulates the physiological loading, may improve the prediction of fragility. To test this, we developed a quantitative computed tomography (QCT)‐based FE model of the vertebra and applied it to a dataset of MM patients with and without prevalent fracture. FE models were generated from vertebral QCT scans of the T12 (T11 if T12 was fractured) of 104 MM patients, 45 with fracture and 59 without, using a low‐dose scan protocol (1.5 mm slice thickness, 4.0 to 6.5 mSv effective dose). A calibration phantom enabled the conversion of the CT Hounsfield units to FE material properties. Compressive loading of the vertebral body was simulated and the stiffness, yield load, and work to yield determined. To compare the parameters between fracture and nonfracture groups, t tests were used, and standardized odds ratios (sOR, normalized to standard deviation) and 95% confidence intervals were calculated. FE parameters were compared to mineral and structural parameters using linear regression. Patients with fracture showed lower vertebral stiffness (–15.2%; p = 0.010; sOR = 1.73; 95% CI, 1.11 to 2.70), yield force (–21.5%; p = 0.002; sOR = 2.09; 95% CI, 1.27 to 3.43), and work to yield (–27.4%; p = 0.001; sOR = 2.28; 95% CI, 1.33 to 3.92) compared to nonfracture patients. All parameters correlated significantly with vBMD (stiffness: R 2 = 0.57, yield force: R 2 = 0.59, work to yield: R 2 = 0.50, p < 0.001), BV/TV (stiffness: R 2 = 0.56, yield force: R 2 = 0.58, work to yield: R 2 = 0.49, p < 0.001), and Tb.Sp (stiffness: R 2 = 0.51, yield force: R 2 = 0.53, work to yield: R 2 = 0.45, p < 0.001). FE modeling identified MM patients with compromised mechanical integrity of the vertebra. Higher sOR values were obtained for the biomechanical compared to structural or mineral measures, suggesting that FE modeling improves fragility assessment in these patients. © 2016 American Society for Bone and Mineral Research.